1/4(k)+3=6

Simple and best practice solution for 1/4(k)+3=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1/4(k)+3=6 equation:



1/4(k)+3=6
We move all terms to the left:
1/4(k)+3-(6)=0
Domain of the equation: 4k!=0
k!=0/4
k!=0
k∈R
We add all the numbers together, and all the variables
1/4k-3=0
We multiply all the terms by the denominator
-3*4k+1=0
Wy multiply elements
-12k+1=0
We move all terms containing k to the left, all other terms to the right
-12k=-1
k=-1/-12
k=1/12

See similar equations:

| 4z+(7z+2)=90 | | 49+z=530 | | P-10=6p-6p | | X÷2+3y÷5-1÷2=0 | | 12x-6=3- | | -1/3(6h+15)=15 | | 2x^+8x+9=0 | | X/2+3y/5-1/2=0 | | 2n-25=-n-50 | | 4(2x-1)+3=6x-19 | | 5/6x2=4/5x3 | | 2n-16=-n-100 | | 15(2+k)=420 | | -9d=99 | | (x-3)/(4x+1)=0 | | 3(x-7)+5(x+4)=15 | | (x-3)/(4x-1)=0 | | 8-x/3=5/2 | | 45=4v-11 | | 4(2x-1)+3=6x-1 | | -11x+2x(x-3)+7x=5x-6 | | 4(2x-1)+3=6x-14 | | 13+2/3(x-8)+10x=7x=39 | | 1t-3/4=5/6 | | (y^2​-9)(y^2​​−4)=0 | | 10-(3z-4)=6-4z | | 12x-9=2x+63 | | y^2​​−9)(y^​2​​−4)=0 | | 6+12k=-10-4k | | y−4=5.4 | | 4(2x-1)+3=6x-17 | | 10n+35=28n+35 |

Equations solver categories